Հայերէնէ անգլերէն զրուցատրութիւն - Խպլիկեան, Զեփիւռ (ԳԱԱ ԼԻ հրատ․)
Учебники - практические пособия, имеющие большое значение для обучения иностранному языку. Цель нашего исследования является наблюдение за изменением или развитием западноармянского языка с 1913 по 1963 год. Сравнительный параллельный анализ учебников, изданных в два разных года и в двух разных местах, показал, что за 50 лет западноармянский язык претерпел явные изменения как в словарном запасе, так и в структуре слов. Подобные исследования и экспертизы могут способствовать изучению языка и обогащению словарного запаса. Textbooks are practical textbooks of great importance for teaching a foreign language. Printed publications that teach a foreign language and provide the opportunity to express oneself in it. Although the purpose of Armenian-English textbooks is to teach English, for us it has another importance: to observe the change or development of Western Armenian from 1913 to 1963. A comparative parallel examination of textbooks published in two different years and in two different places showed that during 50 years, Western Armenian has undergone a clear change in both vocabulary and word structure. Such studies and examinations can contribute to the research of the language and the enrichment of vocabulary.
Keywords: Արեւմտահայերէն; Զրուցարան